Problematika Kompetensi di Kalangan Guru Pendidikan Anak Usia Dini (PAUD) di Indonesia - khairiah khairiah; Diana Anggraini; Ulya Rahmanita; Okda Jumanti; Murudian Wijiati; Vevi Asri Lestari (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2021)
Abstract: Teacher competence in Indonesia has created problems among Early Childhood Education (PAUD) teachers. Some PAUD teachers already have competence in line with the standards and professional code of ethics of teachers, and some others experience problems in carrying out their main duties, functions and responsibilities as professional teachers. The general objective, apart from mapping the problems of teacher competence, is also to analyze the reasons for the problems among PAUD teachers. While the specific purpose of analyzing; (1) the problem of pedagogic competence; (2) personality competence problems; (3) the problem of professional competence; and (4) the problem of social competence. Using descriptive qualitative methods to explore primary data and secondary data. The results showed: (1) there are still some PAUD teachers who have not met the pedagogic competency standards optimally; (2) there are still some PAUD teachers who have not met the personality competency standards optimally; (3) there are still PAUD teachers who have not met professional competency standards optimally; and (4) there are still some PAUD teachers who do not have optimal social competence standards. This paper can be concluded that there has been a problem of teacher competence among PAUD teachers due to the limited ability of teachers to carry out their main tasks, functions and responsibilities in carrying out their obligations and rights in learning. So that this paper can suggest, further research is needed by paying attention to comparative aspects of regionalism based on varied data, so that more accurate policies can be formulated in overcoming competency problems among PAUD teachers.Keywords: Problematics, Competence, Among PAUD Teachers, in IndonesiaÂ Abstrak: Kompetensi guru di Indonesia telah menciptakan problematika di kalangan guru Pendidikan Anak Usia Dini (PAUD). Sebahagian guru PAUD telah memiliki kompetensi sejalan dengan standard dan kode etik professional guru, dan sebahagian yang lain mengalami problematika dalam menjalankan tugas pokok, fungsi dantanggungjawabnya sebagai guru professionalnya. Tujuan umum selain memetakan problematika kompetensi guru juga menganalisis alasan terjadinya problematika di kalangan guru PAUD. Sedangkan tujuan khusus menganalisis; (1) problematika kompetensi pedagogic; (2) problematika kompetensi kepribadian; (3) problematika kompetensi professional; dan (4) problematika kompetensi social. Menggunakan metode kualitatif deskriptif untuk menggali data primer dan data sekunder. Hasil penelitian menunjukkan: (1) masih terdapat sebahagian guru PAUD yang belum memenuhi standar kompetensi pedagogic secara optimal; (2) masih terdapat sebahagian guru PAUD yang belum memenuhi standar kompetensi kepribadianÂ secara optimal; (3) masih terdapat guru PAUD yang belum memnuhi standar kompetensi professional secara optimal; dan (4) masih terdapat sebahagian guru PAUD yang belum memiliki standar kompetensi social secara optimal. Tulisan ini dapat disimpulkan bahwa telah terjadi problematikan kompetensi guru di kalangan guru PAUD yang disebabkan atas keterbatasan kemampuan guru dalam menjalankan tugas pokok, fungsi dan tanggungjawab dalam menjalankan kewajiban dan haknya dalam pembelajaran. Sehingga tulisan ini dapat menyarankan, diperlukan adanya peneliti lanjutan dengan memperhatikan aspek komparasi secara kewilayahan dengan bersumber pada data yang bervariasi, sehingga kebijakan yang lebih akurat dapat dirumuskan dalam mengatasi problematika kompetensi di kalangan guru PAUD.Â Kata kunci : Problematika, Kompetensi, Dikalangan Guru PAUD, di Indonesia